Iron Oxide-Decorated Carbon for Supercapacitor Anodes with Ultrahigh Energy Density and Outstanding Cycling Stability - Guan, Cao (2016)
Supercapacitor with ultrahigh energy density (e.g., comparable with those of rechargeable batteries) and long cycling ability (>50000 cycles) is attractive for the next-generation energy storage devices. The energy density of carbonaceous material electrodes can be effectively improved by combining with certain metal oxides/hydroxides, but many at the expenses of power density and long-time cycling stability. To achieve an optimized overall electrochemical performance, rationally designed electrode structures with proper control in metal oxide/carbon are highly desirable. Here we have successfully realized an ultrahigh-energy and long-life supercapacitor anode by developing a hierarchical graphite foam–carbon nanotube framework and coating the surface with a thin layer of iron oxide (GF–CNT@Fe2O3). The full cell of anode based on this structure gives rise to a high energy of ∼74.7 Wh/kg at a power of ∼1400 W/kg, and ∼95.4% of the capacitance can be retained after 50000 cycles of charge–discharge. These performance features are superior among those reported for metal oxide based supercapacitors, making it a promising candidate for the next generation of high-performance electrochemical energy storage.